UPAYA PEMERINTAH KANADA DALAM MENINGKATKAN KESETARAAN GENDER DI IRAK MELALUI PENDEKATAN FEMINISME TAHUN 2017-2023 - Khansa Adilla Rinda Putri; Januari Pratama Nurratri Trisnaningtyas (Halu Oleo University, 2025)
Canada has implemented various initiatives in Iraq focused on combating gender-based violence and discrimination. In this article, Canada implemented multiple initiatives to improve women's equality in Iraq between 2017 and 2023 by launching programs designed to reduce gender-based violence and discrimination, in line with the Feminist International Assistance Policy (FIAP). This article employs a qualitative research methodology, utilizing concepts such as Gender Inequality, Feminist Foreign Policy, and the 3R framework (Women's Rights, Representation, Resources) to analyze the Canadian government's efforts toward achieving gender equality in Iraq. The findings indicate that FIAP has played a significant role in increasing Iraqi women's participation in public life and the success of initiatives targeting gender inequality. Canada's multifaceted approach has included establishing women's hotlines, providing legal consultation, and supporting women's economic empowerment. This research contributes to a deeper understanding of how feminist foreign policy can be effectively implemented to achieve gender equality in developing countries. The study demonstrates the potential of FIAP as an impactful solution for addressing persistent gender disparities in various international contexts.